Avaliação da adsorção de Cobre(II) e Cromo(III) utilizando resíduos de mármore branco como material adsorvente não convencional e de baixo custo - Guimarães, Tiago (2018)
The adsorption process of Cu (II) and Cr (III) ions on white marble residue was investigated by batch experiments. The studies were carried out to identify the zero charge point (PCZ) of adsorbent material, time and equilibrium concentrations of Cu (II) a